2011
DOI: 10.1159/000329433
|View full text |Cite
|
Sign up to set email alerts
|

Does Smoking Have a Significant Impact on Early Irritant Hand Dermatitis in Metal Workers?

Abstract: Background: Although they know the long-term complications of smoking, many smokers require additional motivation for entering a smoking cessation programme. At the same time, smoking is considered a possible promoting factor for various skin diseases. Objective: The present study assesses the impact of smoking on occupational hand dermatitis in a high-risk population. Material and Methods: 1,355 metal workers, 97.3% of them shift workers, took part in a standardized interview and a dermatological examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 67 publications
2
34
1
3
Order By: Relevance
“…Three studies found a statistically significant positive association between tobacco smoking and HE with respect to prevalence (27)(28)(29), and one found no clear association, but a slightly increased risk of HE in heavy smokers in one subgroup, along with a potential protective association in another subgroup (30). Three studies found no association between tobacco smoking and HE prevalence (31)(32)(33), but, in one of these, smoking was linked to severe eczema (32), and in another non-smoking was linked to more severe eczema (33).…”
Section: Results Of Studies On He and Tobacco Smoking In Occupationalmentioning
confidence: 97%
See 4 more Smart Citations
“…Three studies found a statistically significant positive association between tobacco smoking and HE with respect to prevalence (27)(28)(29), and one found no clear association, but a slightly increased risk of HE in heavy smokers in one subgroup, along with a potential protective association in another subgroup (30). Three studies found no association between tobacco smoking and HE prevalence (31)(32)(33), but, in one of these, smoking was linked to severe eczema (32), and in another non-smoking was linked to more severe eczema (33).…”
Section: Results Of Studies On He and Tobacco Smoking In Occupationalmentioning
confidence: 97%
“…Kütting et al (27) studied 1355 metalworkers, mostly males, and found statistically significantly higher scores for erythematous skin lesions on both hands in smokers than in non-smokers at baseline (p = 0.016). In a 1-year follow-up, which included 800 male metalworkers, significantly more smokers than non-smokers reported episodes of dyshidrotic HE (p = 0.027).…”
Section: Results Of Studies On He and Tobacco Smoking In Occupationalmentioning
confidence: 99%
See 3 more Smart Citations